2023
DOI: 10.1186/s13741-023-00321-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of goal-directed fluid management guided by a non-invasive device on the incidence of postoperative complications in neurosurgery: a pilot and feasibility randomized controlled trial

Abstract: Background The positive effects of goal-directed hemodynamic therapy (GDHT) on patient-orientated outcomes have been demonstrated in various clinical scenarios; however, the effects of fluid management in neurosurgery remain unclear. Therefore, this study was aimed at assessing the safety and feasibility of GDHT using non-invasive hemodynamic monitoring in elective neurosurgery. The incidence of postoperative complications was compared between GDHT and control groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…CI = confidence interval, FEM = fixed effects model; GDFT = goal-directed fluid therapy, REM = random effects model, RoB = risk of bias, Std = standard care Secondary outcomes: Postoperative complications: Six of the included RCTs reported the incidence of overall postoperative complications. [ 19 22 24 25 26 28 ] The pooled estimate revealed that GDFT patients had a significantly lower risk of postoperative complications than the control group [RR (95% CI) = 0.67 (0.54, 0.82), 95% PI = 0.39, 1.41, I 2 = 37%] [ Figure 2 b]. Pulmonary complications were reported in seven studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CI = confidence interval, FEM = fixed effects model; GDFT = goal-directed fluid therapy, REM = random effects model, RoB = risk of bias, Std = standard care Secondary outcomes: Postoperative complications: Six of the included RCTs reported the incidence of overall postoperative complications. [ 19 22 24 25 26 28 ] The pooled estimate revealed that GDFT patients had a significantly lower risk of postoperative complications than the control group [RR (95% CI) = 0.67 (0.54, 0.82), 95% PI = 0.39, 1.41, I 2 = 37%] [ Figure 2 b]. Pulmonary complications were reported in seven studies.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary complications were reported in seven studies. [ 19 21 22 24 25 26 28 ] The pooled estimate showed a significant reduction in pulmonary complications with the use of GDFT compared to the control group [RR (95% CI) = 0.55 (0.38, 0.79), 95% PI = 0.35, 1.10, I 2 = 0%] [ Figure 2 c]. Renal complications were reported in three studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations